Estudo fitoquímico de Galianthe ramosa E. L. Cabral (Rubiaceae) - Freitas, Carla Santos de (2011)
Galianthe ramosa is a shrub of Rubiaceae family (tribe Spermacoceae) with occurrence on Brazilian Cerrado. Phytochemical studies of Rubiaceae shows a wide variety of secundary metabolites with large biological potential and several species are used on folk medicine or as phytotherapy. The only chemical study about this genera, G. brasiliensis describes iridoids isolation. In our continuing chemical and biological investigations of plants from the family Rubiaceae from Cerrado, herein we report the isolation of new alkaloids 1 and 2, together with the known epi-catechin, ursolic acid and oleanolic acid. Besides we propose a biogenic route for new alkaloids because they have been present a new terpene portion. Their structures were determined by IR, HRESIMS, and 1D and 2D NMR experiments, and antioxidant activities, evaluated by assaying the free radical scavenging capacity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical as substrate. The antioxidant activities of crude extract from flowers, leaves, roots and branches showed weakly activities which EC50 105, 107, 109 and 110 μg/mL respectively.